2019
DOI: 10.1242/jeb.201954
|View full text |Cite
|
Sign up to set email alerts
|

Maternal food supplementation and perceived predation risk modify egg composition and eggshell traits but not offspring condition

Abstract: Mothers may vary resource allocation to eggs and embryos, which may affect offspring fitness and prepare them for future environmental conditions. The effects of food availability and predation risk on reproduction have been extensively studied, yet their simultaneous impacts on reproductive investment and offspring early life conditions are still unclear. We experimentally manipulated these key environmental elements using a 2×2 full factorial design in wild, free-living pied flycatchers (Ficedula hypoleuca),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Two studies on species of flycatchers addressed food availability and eggshell traits. Morosinotto et al (2019) found that Pied Flycatchers supplemented with food had thicker eggshells than those not supplemented with food, suggesting that they were able to invest more resources in eggshell development. Additionally, female Collared Flycatchers ( Ficedula albicollis ) that were in better condition laid thicker eggshells (Hargitai et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies on species of flycatchers addressed food availability and eggshell traits. Morosinotto et al (2019) found that Pied Flycatchers supplemented with food had thicker eggshells than those not supplemented with food, suggesting that they were able to invest more resources in eggshell development. Additionally, female Collared Flycatchers ( Ficedula albicollis ) that were in better condition laid thicker eggshells (Hargitai et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other prey responses, such as delaying development, may be compensatory, ameliorating the costs of predator avoidance (Thaler et al., 2012). One type of non‐consumptive effect of predators on prey occurs when mothers exposed to predators change the quantity (hereafter referred to as density) or the quality (hereafter referred to as condition or provisioning) of their offspring (Morosinotto et al., 2019). Predator exposure can alter investment in offspring as parents have less resources to invest in reproduction because they fed less or invested more energy in their own protection, or because of adaptive reproductive allocation decisions.…”
Section: Introductionmentioning
confidence: 99%